Deconstructing the Glaser-Strauss Dilemma: Integrative Discussion about the Grounded Theory in Management - Conejero, Maria Carolina; MacLennan, Maria Laura Ferranty (Organizações & Sociedade, 2023)
The Grounded Theory was developed in the 1960s by sociologists Barney Glaser and Anselm Strauss as methodological or research style. New investigative paths have emerged from Grounded Theory application. The aim of the present study is to highlight the antagonism between Glaser and Strauss from a conceptual complementary perspective that opened room for a highly structured and inherently flexible methodology based on the integrative approach. The goal of the Grounded Theory is to develop theories based on systematically collected and analyzed empirical data. The classical approach proved to be excessively subjective to meet empirical research demands in management, overtime. Accordingly, several authors advocate for Strauss and Corbin’s (1990) ideas. The current essay-style study focuses on proposing and assessing an integrative approach framework for the Grounded Theory. Emphasis is given to the complementary qualities suggested by these authors, which are treated as non-exclusionary, despite being influenced by both Strauss and Corbin’s (1998) positivist style and Glaser and Strauss’ (1967) interpretive style. Furthermore, this theory adheres to the fundamental principle of the classical approach, although it emerged from the research process. This methodology’s application can be a promising option for scientific development, since it can disclose potentialities that give researchers flexibility and freedom to create. Thus, ontological and methodological assumptions are choices made by researchers, themselves, since they can gather research methods (mixed-methodology) and follow the combined and sequential use of quantitative and qualitative techniques to create well-founded theories.